Analysis of Antioxidant Activity, Vitamin C, and Lactic Acid of Yogurt Made Form Cow and Goat Milk Used Electric Shock and Conventional Methods - Endah Budi Permana Putri; Margareta Amelia Iko Ardania (Universitas Dr Soetomo, 2022)
Along with raising public awareness about health and increasing yogurt consumption .Fermented dairy products are considered beneficial foods for the health of human beings. One of them is yogurt which is a healthy drink made from milk with fermentation processing. The research aimed to analysis of antioxidant activity, vitamin C, and Lactic Acid of yogurt made from cow and goat milk. This study is a pure experimental study using a completely randomized design research, using 2 groups of samples, namely the sample with the electric shock processing method and the sample with conventional processing with 3 repetitions. The data obtained will be presented in tabular form and will be checked using the One Way Anova test. If there are differences, the test will continue with the Ducan test. Based on the results of the research analysis of antioxidant activity, vitamin C and lactic acid in goat's milk yogurt and cow's milk with differences in processing, namely the electric shock method and the conventional method had a statistically significant difference, namely with a p-value (0.00) where the value was ≤ α (0.05) which means that there is a significant difference in the average value of antioxidant activity, vitamin C and lactic acid in each sample. In this study it can be concluded that there are significant differences in the four samples. The best value in this study was found in goat milk yogurt with the electric shock method and the lowest value was found in conventional cow's milk yogurt in each analysis carried out, namely the analysis of antioxidant activity, levels of Vitamin C and lactic acid.